Preliminary Note on Artificial Ripening of the Immature Fruits of Broussonetia papyrifera, Vent. (the Paper Mulberry Tree) - Dabral, S. N.; Kadambi, K. (Indian Forester, 1954)
Very little work has been done on the artificial ripening of unripe fruits of forest trees. This note describes the results of treating such fruits of Broussonelia papyrijera with Ethylene gas. Both the germinative capacity and vigour of the seeds improved as a result of the treatment.